Comparative seismic performance evaluation of RC dual system buildings under NBC 105:2025 and IS 1893 (Part I):2025 across varying heights - Shrivastav , Mantu; Shrestha, Rojseen; Pal, Raju (Journal of Innovations in Engineering Education, 2026)
This paper provides a comparative seismic performance evaluation of reinforced concrete (RC) dual system buildings (4, 8, and 16 stories) modeled under the newly updated NBC 105:2025 and IS 1893 (Part I):2025. The structures were analyzed using the response spectrum method, considering Soil Type D for NBC 105:2025 and the newly introduced Zone VI parameters with Site Class D for IS 1893 (Part I):2025 to represent extreme regional seismic demands. Results indicate a significant shift in conservatism; contrary to historical trends, the updated Indian standard now yields higher seismic demands across all heights. This increased conservatism is primarily rooted in intensified seismic load estimation rather than detailing alone. Specifically, the introduction of Zone VI with a high seismic zone factor (Z=0.75) and a more aggressive spectral acceleration plateau for Site Class D (Sa/g=2.5) creates a significantly more rigorous hazard envelope than the current Nepalese mapping. Furthermore, while NBC 105:2025 utilizes refined, decoupled ductility and overstrength factors, the total magnitude of the hazard parameters in the Indian code governs the design force requirements. Quantitatively, the IS 1893 (Part I):2025 base shear is 1.92 and 2.11 times greater for 4 and 8-storey buildings, respectively. Lateral displacements mirror this trend, recorded at 32 mm (IS 1893 (Part I):2025) versus 14 mm (NBC 105:2025) for the 4-storey model. While results for the 16-storey building show a trend toward convergence (233 mm vs 223 mm), the Indian standard remains the governing case. The study emphasizes the increased stiffness and strength requirements necessitated by the more conservative force demands of the 2025 Indian code update.